Analysis of critical thinking skill profile on the concept of simple harmonic motion using two tier instrument test. (June 2020) - Umam, A; Suparmi,; Sukarmin,
Abstract: The purpose of thisstudy was to analyze critical thinking skills profile of seniorhigh school learners, especially in eleventh grade. This study used qualitative descriptive study to analyse critical thinking skills profile. The subject of this study were eleventh grade student of sience classes in Public Senior Hight School no 4 Surakarta with 87 students whose registered as student in the 2018/2019 school year. Sampling in this study used random sampling technique. The instrument test used in this study was two tier test. The instrumentuse indicatorscritical thinking skills developed by Ennis with 5 indicators and 7 sub-indicator. Instrument test consists two stages, the first stage was multiple-choice questions and the second stage was an open-ended free response question which was the reason forthe answer of the student to the question at the first stage. The result of this study showed that critical thinking skill were still low. In every indicator critical thingking skill were 42% for basic clarification, 29% basic for decision or basic support, 27% for inference, 25% advanced clarification, 24% stategy and tactic. Critical thinking skills were low because learning was still centered on the teacher.